2015
DOI: 10.2106/jbjs.n.00881
|View full text |Cite
|
Sign up to set email alerts
|

Early Versus Late Culture Growth of Propionibacterium acnes in Revision Shoulder Arthroplasty

Abstract: Diagnostic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(62 citation statements)
references
References 24 publications
5
57
0
Order By: Relevance
“…Our results may not be transposable to PJI infections other than hip and knee. As the proportion of skin commensals like C. acnes is higher in shoulder PJI, further studies are needed to describe the time of growth of bacteria found in other PJI locations [19,21].…”
Section: Discussionmentioning
confidence: 99%
“…Our results may not be transposable to PJI infections other than hip and knee. As the proportion of skin commensals like C. acnes is higher in shoulder PJI, further studies are needed to describe the time of growth of bacteria found in other PJI locations [19,21].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the study showed that a prolonged cultivation time of Ͼ10 days did not improve sensitivity. Therefore, Frangiamore et al (3) recommended that a routine cultivation time of 10 days is optimal to ensure accurate diagnosis of P. acnes infections. Our data support this recommendation.…”
Section: Fig 2 Proportions Of First (A) or Second (Confirmation) (B) mentioning
confidence: 99%
“…However, it may also cause bone and joint infections, including implant-associated infections. P. acnes has been recognized as an emerging cause of shoulder infections (2,3) and is among the most common pathogens isolated in shoulder periprosthetic joint infections (PJI) (4,5). P. acnes has also been implicated in other biofilm-related infections (6)(7)(8), such as cardiovascular implantassociated infections (9), spinal osteomyelitis (10,11), and endophthalmitis (12,13).…”
mentioning
confidence: 99%
“…Propionibacterium acnes is a gram‐positive bacillus that resides in sebum glands. It is a common contaminant in shoulder surgery, and a potential pathogen in post‐operative shoulder infections . Recent studies indicate a high incidence of P. acnes in the subdermal layer, and it is postulated that the organism may be carried into the deeper tissues during surgery by instruments or by hand …”
Section: Discussionmentioning
confidence: 99%